Measurement of long-range pseudorapidity correlations and azimuthal harmonics in $\sqrt{s_{NN}}=5.02$ TeV proton-lead collisions with the ATLAS detector - ATLAS collaboration (2891 authors) (2014)
Measurements of two-particle correlation functions and the first five azimuthal harmonics, $v_1$ to $v_5$, are presented, using 28 $nb^{-1}$ of $p$+Pb collisions at a nucleon-nucleon center-of-mass energy of $\sqrt{s_{NN}}=5.02$ TeV measured with the ATLAS detector at the LHC. Significant long-range "ridge-like" correlations are observed for pairs with small relative azimuthal angle ($|Δφ|<π/3$) and back-to-back pairs ($|Δφ| > 2π/3$) over the transverse momentum range $0.4 < p_{\rm T} < 12$ GeV and in different intervals of event activity. The event activity is defined by either the number of reconstructed tracks or the total transverse energy on the Pb-fragmentation side. The azimuthal structure of such long-range correlations is Fourier decomposed to obtain the harmonics $v_n$ as a function of $p_{\rm T}$ and event activity. The extracted $v_n$ values for $n=2$ to 5 decrease with $n$. The $v_2$ and $v_3$ values are found to be positive in the measured $p_{\rm T}$ range. The $v_1$ is also measured as a function of $p_{\rm T}$ and is observed to change sign around $p_{\rm T}≈ 1.5$-2.0 GeV and then increase to about 0.1 for $p_{\rm T}>4$ GeV. The $v_2(p_{\rm T})$, $v_3(p_{\rm T})$ and $v_4(p_{\rm T})$ are compared to the $v_n$ coefficients in Pb+Pb collisions at $\sqrt{s_{NN}} =2.76$ TeV with similar event multiplicities. Reasonable agreement is observed after accounting for the difference in the average $p_{\rm T}$ of particles produced in the two collision systems.